Delayed EIP and EDC tendon rupture after distal radius fracture - Richard McKinney; Gabrielle Allred; Peter Tang (Journal of Orthopaedic Reports)
Background: Distal radius fractures are a common presentation in the orthopedic practice. There is extensive literature on the appropriate management of these injuries based on age, displacement, and other factors. Attritional tendon ruptures are a rare but described complication in both surgically and closed managed fractures. We report a case of delayed extensor indicis and extensor digitorum tendon rupture after conservatively managed distal radius fracture. Case report: A 68 year old female presents with a right wrist injury after a mechanical fall. She was found to have an isolated right distal radius fracture with minimal displacement. She was immobilized in a splint for 5 weeks and progressed to full weightbearing activity at 8 weeks. 14 weeks after injury, she suffered attritional rupture of the EIP and EDC tendons to the index finger. Intraoperatively impending rupture of the EPL tendon was also noted. She successfully underwent tendon reconstruction but had persistent index extensor lag at final follow-up. Literature review: There are 643,000 distal radius fractures annually, with an extensor tendon rupture incidence of up to 5% in those treated without surgery. This most commonly involves the EPL tendon. Tendon reconstruction and tendon transfer are the mainstays of operative management of these complications. Clinical relevance: Distal radius fractures with attritional tendon ruptures present a relatively rare but challenging problem. This case reports one of the only examples of isolated index extensor rupture in an adult and highlights the importance of clinical vigilance and patient counseling on the possible complications.